Breast Feeding as a Problem of the XXI Century - G. А. Kulakova; N. А. Solov'eva; E. А. Kurmaeva ("Paediatrician" Publishers LLC, 2014)
In the article the most frequent problems of breast feeding on a pediatric site are considered. The assessment is given to quality of knowledge and participation extent of local crew staff in «mother-child» system when forming lactation dominant at a nursing woman, correction variants of this work are offered. Among the main obstacles for feeding the child by breast milk there is mother anxiety concerning the amount of lactated milk. The authors of the article pay attention to necessity and possibility of the differentiated approach to the baby cry, and also to importance of mother training in order to make her understand the so-called hungry cry. The balanced approach to supplementary feeding prescription, and in case of its need for the purpose of breast feeding maintenance, the use of a dummy imitating the act of breastfeeding are necessary.